O procedimento de tradução como fundamento da educação nos museus de arte - Consiglio, Thiago (Universidade Federal de São Carlos, 2019)
This research focuses the theme of education at art museums and seeks to discuss the foundations of the education practiced by museums through the concept of translation. The main objective of the dissertation is, through bibliographical research, to answer the question-problem: “in what way translation can be a foundation of educational pratice at art museums?”. For that, the work reframed the concept of translation through three procedures: literary, educational and epistemological; briefly raised the historical process of museum education; and also problematized historical and plural museums perspectives in relation with the reframed conception of translation. The study open with the idea that translation is: a development of a new authorship text; an effort in apreehension of knowledge; and a link between multiple views in knowledge production. As a conclusion, the work acknowledged that translation can support an emancipatory educational practice at art museums concerned about the importance of language, and as an essentially open model that is made through process and plurality.
The translation procedure as a foundation of education ir art museums
Keywords: Educação museal; Tradução; Museu de arte; Epistemologia; Museum education; Translation; Art museum; Epistemology; LINGUISTICA, LETRAS E ARTES::ARTES::EDUCACAO ARTISTICA; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO